Boxitects - Smith, Kim, 1986- (Clarion Books, Houghton Mifflin Harcourt, 2020)
Meg goes to Maker School to hone her talent for building with boxes, but when Simone, another boxitect, arrives they become so competitive they nearly fail in the annual Maker Match.